Extremely high photoconductivity ultraviolet-light sensor using amorphous In–Ga–Zn–O thin-film-transistor - Park, Jin Seong; Seo, Hyung Tak; Park, Jea Gun (Journal of the Korean Physical Society, 2021)
An amorphous (α) indium-gallium-zinc-oxide (IGZO) thin-film-transistor (TFT) was developed as a precise ultraviolet-light (UV-light) sensor, which is extremely sensitive to photoconductivity. A higher absorption of UV-light via a longer UV-light irradiation time and a higher UV-light intensity shifted the threshold voltage (Vth) to a negatively higher voltage and then saturated above a specific UV-light irradiation time. Particularly, the photoconductivity (i.e., Vth) shifts were evidently dependent on the oxygen vacancy (VO)-induced defect density of an ALD α-IGZO channel; in turn, a higher VO-induced defect density led to a higher photoconductivity shift. Additionally, the Vth saturation time in an ALD α-IGZO TFT decreased rapidly with increasing UV-light intensity; in particular, a higher VO-induced defect density presented a smaller decay constant of the Vth saturation time. Furthermore, the Vth after stopping the UV-light irradiation was rapidly recovered to the condition as without UV-light irradiation condition and a higher VO-induced defect density exhibited a longer recovery time.
Keywords: ALD; IGZO; Photoconductivity; TFT; UV sensor